Siyasal propaganda: 2007 ve 2011 seçimlerinin analizi - Bölükbaşı, Mustafa (My University, 2019)
This dissertation examines the function and transformation of political propaganda in contemporary democratic regimes. It asserts that political propaganda resembles increasingly to commercial campaigns. This study links this transformation with the models of political party. Nowadays, political parties in most of the competitive regimes have demonstrated two main tendencies. One of them is that organizational structures of political parties have been eroded and increasingly become leaderoriented. The effect of party organizations on party activities, particularly electing candidates and decision-making process, has decreased. Party competition and loyalty to the party have been superseded by leader competition and personal loyalty to the leader. Thus, election campaigns, increasingly have been focused on personalities of leaders. Parties have maintained their central roles at establishing communication and influence networks, financing and providing voluntary support etc., but they have become campaign tools of leaders. Secondly, election campaigns, increasingly, have been adapted to marketing techniques. Rather than following ideological programmes, political parties have carried out winning strategies. In order to analyse “voters in the political market”, political parties have required marketing techniques and professionals. This study, by applying a descriptive research, aims at finding out general characteristics of 2007 and 2011 election campaigns carried out by JDP and RPP in terms of transformation of political propaganda. In this research, different kinds of materials have been used like party programmes and statutes, election manifestos, parliament speeches, election songs, slogans, meeting speeches, television debates, political ads, opinion polls, reports etc. Findings of this study have shown that the professionalization of election campaigns in Turkey have been increasingly proceeded in terms of financing, technology usage, media communication, personalization and roles of professionals.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Political propaganda; Political parties; Elections campaigns; Siyasi propaganda; Siyasi partiler; Seçim kampanyaları; JDP; RPP; AKP; CHP